Analysis of SARS-CoV-2 Spike Protein Variants with Recombinant Reporter Viruses Created from a Bacmid System - Cordsmeier, Arne; Jungnickl, Doris; Herrmann, Alexandra; Korn, Klaus; Enßer, Armin (International Journal of Molecular Sciences, 2023)
SARS-CoV-2, the causative agent of COVID-19, has spread around the world with more than 700 million cases and 6.8 million deaths. Various variants of concern (VoC) have emerged due to mutations and recombination and concurrent selection for increased viral fitness and immune evasion. The viral protein that primarily determines the pathogenicity, infectivity, and transmissibility is the Spike protein. To analyze the specific impact of variant Spike proteins on infection dynamics, we constructed SARS-CoV-2 with a uniform B.1 backbone but with alternative Spike proteins. In addition, ORF6 was replaced by EYFP as a biological safety measure, and for use of this well-established reporter. We show that namely the delta variant Spike proteins cause a distinct phenotype from the wild type (B.1, D614G) and other variants of concern. Furthermore, we demonstrate that the omicron BA.1 Spike results in lower viral loads and a less efficient spread in vitro. Finally, we utilized viruses with the two different reporters EYFP and mCherry to establish a competitive growth assay, demonstrating that most but not all Spike variant viruses were able to outcompete wild type SARS-CoV-2 B.1.
CRIS-Team Scopus Importer:2023-05-26
Keywords: SARS-CoV-2; Spike protein; variants of concern

Bornavirus encephalitis as a differential diagnosis to seronegative autoimmune encephalitis - Meier, H.; Bauer, C.; Finkenzeller, W.; Nentwich, J.; Staedt, M.; Steininger, Philipp; Korn, Klaus; Enßer, Armin; Erbguth, F. (Der Nervenarzt, 2022)
CRIS-Team WoS Importer:2022-01-28

Chronic inflammation degrades CD4 T cell immunity to prior vaccines in treated HIV infection - Kießling, Melissa; Cole, John J.; Kübel, Sabrina; Klein, Paulina; Korn, Klaus; Henry, Amy R.; Laboune, Farida; Fourati, Slim; Harrer, Ellen; Harrer, Thomas; Douek, Daniel C.; Überla, Klaus; et al. (Nature Communications, 2024)
To date, our understanding of how HIV infection impacts vaccine-induced cellular immunity is limited. Here, we investigate inflammation, immune activation and antigen-specific T cell responses in HIV-uninfected and antiretroviral-treated HIV-infected people. Our findings highlight lower recall responses of antigen-specific CD4 T cells that correlate with high plasma cytokines levels, T cell hyperactivation and an altered composition of the T subsets enriched with more differentiated cells in the HIV-infected group. Transcriptomic analysis reveals that antigen-specific CD4 T cells of the HIV-infected group have a reduced expression of gene sets previously reported to correlate with vaccine-induced pathogen-specific protective immunity and further identifies a consistent impairment of the IFNα and IFNγ response pathways as mechanism for the functional loss of recall CD4 T cell responses in antiretroviral-treated people. Lastly, in vitro treatment with drugs that reduce inflammation results in higher memory CD4 T cell IFNγ responses. Together, our findings suggest that vaccine-induced cellular immunity may benefit from strategies to counteract inflammation in HIV infection.
CRIS-Team Scopus Importer:2024-12-06

Correction to: Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections (European Journal of Clinical Microbiology & Infectious Diseases, (2021), 10.1007/s10096-021-04285-4) - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
In the originally published version of the article, captions of Figures 1, 2, 3, 4, and 5 have missing figure denominations. The figures are presented here with correct captions. Layout adjustments are also made to Tables 2-5 for readability. The original article has been corrected. (Figure presented.).
CRIS-Team Scopus Importer:2021-07-30

Definition of a New HLA B*52-Restricted Rev CTL Epitope Targeted by an HIV-1-Infected Controller - El Kenz, Boutaina; Schmidt, Katja; Ogungbemi-Alt, Victoria K.; Bergmann, Silke; Steininger, Philipp; Korn, Klaus; Spriewald, Bernd; Harrer, Ellen; Nganou-Makamdop, Krystelle; Harrer, Thomas (Viruses, 2023)
The analysis of T-cell responses in HIV-1-infected controllers may contribute to a better understanding of the protective components of the immune system. Here, we analyzed the HIV-1-specific T-cell response in a 59-year-old HIV-1-infected controller, infected for at least seven years, who presented with low viral loads ranging from <20 copies/mL to 200 copies/mL and normal CD4 counts of >800 cells/µL. In γ-IFN-ELISpot assays using freshly isolated PBMCs, he displayed a very strong polyclonal T-cell response to eight epitopes in Gag, Nef and Rev; with the dominant responses directed against the HLA-B*57-epitope AISPRTLNAW and against a so-far-unknown epitope within Rev. Further analyses using peptide-stimulated T-cell lines in γ-IFN-ELISpot assays delineated the peptide RQRQIRSI (Rev-RI8) as a newly defined HLA-B*52-restricted epitope located within a functionally important region of Rev. Peptide-stimulation assays in 15 HLA-B*52-positive HIV-1-infected subjects, including the controller, demonstrated recognition of the Rev-RI8 epitope in 6/15 subjects. CD4 counts before the start of antiviral therapy were significantly higher in subjects with recognition of the Rev-RI8 epitope. Targeting of the Rev-RI8 epitope in Rev by CTL could contribute to the positive association of HLA-B*52 with a more favorable course of HIV-1-infection.
CRIS-Team Scopus Importer:2023-03-10
Keywords: CTL; elite controller; epitope; HIV-1 infection; HLA B*52; Rev

Detection of asymptomatic SARS-CoV-2 infections in daycare centers, schools, and companies for regional pandemic containment by a PCR testing laboratory cooperative between July 2021 and June 2022 - Bertram, Ralph; Grebenstein, Laura; Gualdi, Stefanie; Seibold, Bernd; Birkmann, Ralf; Korn, Klaus; Bisping, Johannes; Schabik, Ralf (GMS Hygiene and Infection Control, 2022)
As an important element in the regional containment of the COVID-19 pandemic a PCR testing laboratory with a cooperative character was founded in spring 2021 to screen for SARS-CoV-2 in the Nuremberg region, Germany. The aim was to detect asymptomatic infections in day care facilities for children, schools, and companies. The laboratory used an established RT-PCR protocol and analyzed approximately 18,500 pools of up to 25 pooled samples each from gargles or swabs ("lolli-pops") from up to 135 facilities between July 2021 and June 2022. Usually, the participating facilities were informed about positive pools within a few hours. Retention samples from positive pools were usually analyzed on the same day, and the results were reported to the facilities as well as the German Electronic Reporting and Information System (DEMIS). In the laboratory results, both the local incidences and the transition from the Delta-to the Omicron surge in early 2022 were well reflected. It is plausible that about 4,800 secondary infections could be prevented from the approximately 1,570 positive individual samples detected in conjunction with appropriate isolation measures. Such a PCR laboratory, which is characterized by short response times and high flexibility, can thus provide valuable services for regional surveil-lance of infection incidence.
CRIS-Team WoS Importer:2022-12-23

Detection of pre-existing neutralizing antibodies against Ad26 in HIV-1-infected individuals not responding to the Ad26.COV2.S vaccine - Schmidt, Katja; Harrer, Ellen; Schönau, Verena; Simon, David; Kleyer, Arnd; Steininger, Philipp; Korn, Klaus; Schett, Georg; Knobloch, Carina; Nganou-Makamdop, Krystelle; Harrer, Thomas (Infection, 2023)
Purpose: The Ad26.COV2.S vaccine is a replication-incompetent human adenovirus type 26 vector encoding the SARS-CoV-2 spike protein. In a phase 1-2a trial, a single dose of Ad26.COV2.S induced SARS-CoV-2 spike-specific antibodies in ≥ 96% of healthy adults. To investigate vaccine immunogenicity in HIV-1-infection, we measured SARS-CoV-2 spike-specific antibodies in Ad26.COV2.S vaccinated HIV-1-infected patients and analyzed the presence of pre-existing Ad26 neutralizing antibodies. Methods: We included all Ad26.COV2.S vaccinated HIV-1-infected patients of Erlangen HIV cohort fulfilling all inclusion criteria. The study cohort consisted of 15 HIV-1-infected patients and three HIV-1-uninfected subjects who received the Ad26.COV2.S vaccine between April and November 2021. Pre-vaccination sera were collected between October 2014 and June 2021, post-vaccination sera between June and December 2021. Neutralizing antibodies towards Ad26 were determined by a FACS-based inhibition assay measuring the expression of SARS-CoV-2 spike and adenoviral proteins in HEK293T cells after in-vitro transduction with Ad26.COV2.S or the control ChAdOx1-S. Results: Six out of 15 HIV-1-infected patients failed to develop SARS-CoV-2-specific antibodies and four patients developed weak antibody responses after vaccination with Ad26.COV2.S. Pre-vaccination sera of four of the six vaccine non-responders showed neutralizing activity towards Ad26.COV2.S but not toward the ChAdOx1-S vaccine at 1:50 dilution. After Ad26.COV2.S vaccination, 17 of the 18 subjects developed strong Ad26-neutralizing activity and only one of the 18 subjects showed neutralizing activity towards the ChAdOx1-S vaccine. Conclusion: Ad26.COV2.S vaccination showed a high failure rate in HIV-1-infected patients. Pre-existing immunity against Ad26 could be an important contributor to poor vaccine efficacy in a subgroup of patients.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Ad26.COV2.S; Adenovirus 26; HIV-1; Neutralizing antibodies; SARS-CoV-2; SARS-CoV-2 vaccine

Diagnostic performance of four SARS-CoV-2 antibody assays in patients with COVID-19 or with bacterial and non-SARS-CoV-2 viral respiratory infections - Huber, Timo; Steininger, Philipp; Irrgang, Pascal; Korn, Klaus; Tenbusch, Matthias; Diesch, Katharina; Achenbach, Susanne; Kremer, Andreas; Werblow, Marissa; Vetter, Marcel; Bogdan, Christian; Held, Jürgen (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
SARS-CoV-2 antibody assays are used for epidemiological studies and for the assessment of vaccine responses in highly vulnerable patients. So far, data on cross-reactivity of SARS-CoV-2 antibody assays is limited. Here, we compared four enzyme-linked immunosorbent assays (ELISAs; Vircell SARS-CoV-2 IgM/IgA and IgG, Euroimmun SARS-CoV-2 IgA and IgG) for detection of anti-SARS-CoV-2 antibodies in 207 patients with COVID-19, 178 patients with serological evidence of different bacterial infections, 107 patients with confirmed viral respiratory disease, and 80 controls from the pre-COVID-19 era. In COVID-19 patients, the assays showed highest sensitivity in week 3 (Vircell-IgM/A and Euroimmun-IgA: 78.9% each) and after week 7 (Vircell-IgG: 97.9%; Euroimmun-IgG: 92.1%). The antibody indices were higher in patients with fatal disease. In general, IgM/IgA assays had only limited or no benefit over IgG assays. In patients with non-SARS-CoV-2 respiratory infections, IgG assays were more specific than IgM/IgA assays, and bacterial infections were associated with more false-positive results than viral infections. The specificities in bacterial and viral infections were 68.0 and 81.3% (Vircell-IgM/IgA), 84.8 and 96.3% (Euroimmun-IgA), 97.8 and 86.0% (Vircell-IgG), and 97.8 and 99.1% (Euroimmun-IgG), respectively. Sera from patients positive for antibodies against Mycoplasma pneumoniae, Chlamydia psittaci, and Legionella pneumophila yielded particularly high rates of unspecific false-positive results in the IgM/IgA assays, which was revealed by applying a highly specific flow-cytometric assay using HEK 293 T cells expressing the SARS-CoV-2 spike protein. Positive results obtained with anti-SARS-CoV-2 IgM/IgA ELISAs require careful interpretation, especially if there is evidence for prior bacterial respiratory infections.
CRIS-Team Scopus Importer:2021-06-18
Keywords: Antibody; Bacterial infections; Coronavirus; COVID-19; Euroimmun; SARS-CoV-2; Vircell

Early Mortality of Brain Cancer Patients and its Connection to Cytomegalovirus Reactivation During Radiochemotherapy - Goerig, Nicole; Frey, Benjamin; Korn, Klaus; Fleckenstein, Bernhard; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Rühle, Paul-Friedrich; Putz, Florian; Semrau, Sabine; et al. (Clinical Cancer Research, 2020)
PURPOSE: If routine diagnostics are inconclusive, neurologic deterioration and death of patients with brain cancer are attributed to tumor or therapy. Therefore, diagnosing symptoms of encephalopathy caused by human cytomegalovirus (HCMV) reactivation remains uncommon. We investigated the role of HCMV reactivation in neurologic decline and clinical outcome after the start of radiochemotherapy. EXPERIMENTAL DESIGN: HCMV analyses and extended MRI studies including additional independent retrospective neuroradiologic evaluation were performed at predetermined intervals and in case of sudden neurologic decline for 118 adult patients: 63 histologically proven high-grade gliomas, 55 with brain metastases. Immunophenotyping from simultaneously taken whole-blood samples was carried out to detect immune cells serving as prognostic marker for HCMV-associated complications. Symptomatic viremia and overall survival (OS) were the endpoints. RESULTS: Twenty-four percent (28/118) of all patients (12/44 glioblastoma, 3/13 anaplastic astrocytoma; 8/31 non-small cell lung cancer (NSCLC), 13/24 other brain metastases) developed HCMV-viremia during or within 4 weeks after radiotherapy; 21 of 28 patients experienced concurrent major neurologic decline, reversible by antiviral treatment. Identified by immunophenotyping, pretherapeutically low basophil counts predicted a high-risk for HCMV-associated encephalopathy (glioblastoma: P = 0.002, NSCLC: P = 0.02). Median OS was substantially reduced after HCMV-associated encephalopathy without MRI signs of tumor progression [glioblastoma: 99 vs. 570 days (calculated 1-year OS: 22% vs. 69%; P = 0.01) and NSCLC: 47 vs. 219 days (calculated 1-year OS: 0% vs. 32%; P = 0.02)]. CONCLUSIONS: For patients with brain cancer, HCMV reactivation after the start of radiochemotherapy is a frequent risk for cognitively detrimental but treatable encephalopathy and premature death. Routinely performed HCMV diagnostics, assessing basophil counts and study-based anti-viral regimens, are necessary to combat this hidden threat.See related commentary by Lawler et al., p. 3077.
CRIS-Team Scopus Importer:2020-07-17

Erratum to: Bornavirus encephalitis as a differential diagnosis to seronegative autoimmune encephalitis (Der Nervenarzt, (2022), 10.1007/s00115-021-01259-x) Erratum zu: Die Borna-Virus-Enzephalitis als Differenzialdiagnose zur seronegativen Autoimmunenzephalitis (Der Nervenarzt, (2022), 10.1007/s00115-021-01259-x) - Meier, H.; Bauer, C.; Finkenzeller, W.; Nentwich, J.; Städt, M.; Steininger, Philipp; Korn, Klaus; Enßer, Armin; Erbguth, F. (Der Nervenarzt, 2022)
CRIS-Team Scopus Importer:2022-05-06

Estimates and determinants of sars-cov-2 seroprevalence and infection fatality ratio using latent class analysis: The population-based tirschenreuth study in the hardest-hit german county in spring 2020 - Wagner, Ralf; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Berr, Melanie; Einhauser, Sebastian; Schütz, Anja; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Tenbusch, Matthias; Maier, Clara; et al. (Viruses, 2021)
SARS-CoV-2 infection fatality ratios (IFR) remain controversially discussed with implications for political measures. The German county of Tirschenreuth suffered a severe SARS-CoV-2 outbreak in spring 2020, with particularly high case fatality ratio (CFR). To estimate seroprevalence, underreported infections, and IFR for the Tirschenreuth population aged ≥14 years in June/July 2020, we conducted a population-based study including home visits for the elderly, and analyzed 4203 participants for SARS-CoV-2 antibodies via three antibody tests. Latent class analysis yielded 8.6% standardized county-wide seroprevalence, a factor of underreported infections of 5.0, and 2.5% overall IFR. Seroprevalence was two-fold higher among medical workers and one third among current smokers with similar proportions of registered infections. While seroprevalence did not show an age-trend, the factor of underreported infections was 12.2 in the young versus 1.7 for ≥85-year-old. Age-specific IFRs were <0.5% below 60 years of age, 1.0% for age 60–69, and 13.2% for age 70+. Senior care homes accounted for 45% of COVID-19-related deaths, reflected by an IFR of 7.5% among individuals aged 70+ and an overall IFR of 1.4% when excluding senior care home residents from our computation. Our data underscore senior care home infections as key determinant of IFR additionally to age, insufficient targeted testing in the young, and the need for further investigations on behavioral or molecular causes of the fewer infections among current smokers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Antibodies; CLIA; ELISA; Infection fatality ratio; Latent class analysis; SARS-CoV-2; Senior care homes; Seroprevalence; Smoking; Underreported infections

Fatal Puumala Hantavirus Infection in a Patient with Common Variable Immunodeficiency (CVID) - Steininger, Philipp; Herbst, Larissa; Bihlmaier, Karl; Willam, Carsten; Koerper, Sixten; Schrezenmeier, Hubert; Klueter, Harald; Pfister, Frederick; Amann, Kerstin Ute; Weiss, Sabrina; Krueger, Detlev H.; Zimmermann, Robert; et al. (Microorganisms, 2023)
Puumala hantavirus (PUUV) infections usually show a mild or moderate clinical course, but may sometimes also lead to life-threatening disease. Here, we report on a 60-year-old female patient with common variable immunodeficiency (CVID) who developed a fatal PUUV infection with persistent renal failure, thrombocytopenia, and CNS infection with impaired consciousness and tetraparesis. Hantavirus-specific antibodies could not be detected due to the humoral immunodeficiency. Diagnosis and virological monitoring were based on the quantitative detection of PUUV RNA in blood, cerebrospinal fluid, bronchial lavage, and urine, where viral RNA was found over an unusually extended period of one month. Due to clinical deterioration and virus persistence, treatment with ribavirin was initiated. Additionally, fresh frozen plasma (FFP) from convalescent donors with a history of PUUV infection was administered. Despite viral clearance, the clinical condition of the patient did not improve and the patient died on day 81 of hospitalization. This case underlines the importance of the humoral immune response for the course of PUUV disease and illustrates the need for PCR-based virus diagnostics in those patients. Due to its potential antiviral activity, convalescent plasma should be considered in the therapy of severe hantavirus diseases.
CRIS-Team Scopus Importer:2023-03-10
Keywords: common variable immunodeficiency; convalescent plasma; encephalitis; Puumala hantavirus; ribavirin

Herpes simplex virus encephalitis after temporal lobe resection: an infrequent but treatable complication of epilepsy surgery - Martínez-Poles, J.; Toledano, R.; Aledo-Serrano; Korn, Klaus; Coras, Roland; Blümcke, Ingmar; García-Morales, I.; Álvarez-Linera, J.; Gil-Nagel, A. (European Journal of Neurology, 2020)
CRIS-Team Scopus Importer:2020-09-11
Keywords: clinical and diagnostic investigations; encephalitis; epilepsy; imaging; infections; magnetic resonance imaging (MRI); management; neurological disorders; surgery

Increased human herpesvirus-8 neutralizing response during remission from Kaposi’s sarcoma - Byren, Hannah; Holzer, Angela; Müller, Alexander; Korn, Klaus; Backovic, Marija; Harrer, Ellen; Bergmann, Silke; Harrer, Thomas; Neipel, Frank (Journal of General Virology, 2024)
Human herpesvirus-8 (HHV-8), also known as Kaposi’s sarcoma-associated herpesvirus, is a human oncogenic herpesvirus that is responsible for several diseases including Kaposi’s sarcoma (KS). KS prevalence varies dramatically, although emergence increases considerably with human immunodeficiency virus -1 (HIV-1) co-infection, making it one of the most common cancers in HIV-1 patients and sub-Saharan African men, even prior to the HIV-1 epidemic in Africa. Studies have shown that neutralizing antibodies exist in HHV-8-infected sera, which are most likely targeted to viral lytic surface glycoproteins, such as glycoprotein K8.1 (gpK8.1) and gHgL. Fifty-eight HHV-8-positive serum samples were tested for the levels of gpK8.1- and gHgL-binding antibodies and in vitro HHV-8-neutralizing capacity. Each sample was then categorized according to the disease status, which included asymptomatic infection, active KS and remission from KS, and the three measured parameters were compared between the disease groups. We show that neutralizing capacity in infected patient sera increases with remission of KS. Interestingly, antibodies targeting gpK8.1, but not gHgL, were also found to be increased during active disease and remission. Comparison of neutralizing capacity and antibody levels on an individual patient basis revealed that antibody levels, primarily targeting gHgL, are correlated with serum neutralizing response in sub-lingual Kaposi sarcoma (SLK) cells. Adsorption of gHgL or gpK8.1 antibodies from human sera removed the neutralizing response in SLK cells, although some non-specific removal of antibodies from the sera means that this result should be interpreted with caution. Taken collectively, these results suggest that glycoproteins, such as gHgL, are targets for neutralizing antibodies. Furthermore, our data imply that recovery from KS is associated with increased neutralizing capacity, suggesting that neutralizing antibodies may contribute to KS resolution. However, it is vital for further work to be completed in order to elucidate this relationship.
CRIS-Team Scopus Importer:2024-12-13
Keywords: gHgL; gpk8.1; HHV-8; Kaposi's sarcoma; neutralizing antibodies; remission

Lethal Borna disease virus 1 infections of humans and animals – in-depth molecular epidemiology and phylogeography - Ebinger, Arnt; Santos, Pauline D.; Pfaff, Florian; Dürrwald, Ralf; Kolodziejek, Jolanta; Schlottau, Kore; Ruf, Viktoria; Liesche-Starnecker, Friederike; Enßer, Armin; Korn, Klaus; Ulrich, Reiner; Fürstenau, Jenny; et al. (Nature Communications, 2024)
Borna disease virus 1 (BoDV-1) is the causative agent of Borna disease, a fatal neurologic disorder of domestic mammals and humans, resulting from spill-over infection from its natural reservoir host, the bicolored white-toothed shrew (Crocidura leucodon). The known BoDV-1-endemic area is remarkably restricted to parts of Germany, Austria, Switzerland and Liechtenstein. To gain comprehensive data on its occurrence, we analysed diagnostic material from suspected BoDV-1-induced encephalitis cases based on clinical and/or histopathological diagnosis. BoDV-1 infection was confirmed by RT-qPCR in 207 domestic mammals, 28 humans and seven wild shrews. Thereby, this study markedly raises the number of published laboratory-confirmed human BoDV-1 infections and provides a first comprehensive summary. Generation of 136 new BoDV-1 genome sequences from animals and humans facilitated an in-depth phylogeographic analysis, allowing for the definition of risk areas for zoonotic BoDV-1 transmission and facilitating the assessment of geographical infection sources. Consistent with the low mobility of its reservoir host, BoDV-1 sequences showed a remarkable geographic association, with individual phylogenetic clades occupying distinct areas. The closest genetic relatives of most human-derived BoDV-1 sequences were located at distances of less than 40 km, indicating that spill-over transmission from the natural reservoir usually occurs in the patient´s home region.
CRIS-Team Scopus Importer:2024-09-20

Molecular analysis of the 2022 mpox outbreak and antiviral activity of dihydroorotate dehydrogenase inhibitors against orthopoxviruses - Cordsmeier, Arne; Herrmann, Alexandra; Gege, Christian; Kohlhof, Hella; Korn, Klaus; Enßer, Armin (Antiviral Research, 2025)
Monkeypox virus (MPXV) has caused a large pandemic outbreak in 2022 with more than 90.000 confirmed cases and 181 deaths. Notably, signs of microevolution and host adaption have been observed. Here, we demonstrate that viral genomes from Franconia, Bavaria acquired different mutations. Three isolates obtained from diagnostic samples, submitted from suspected Mpox cases, show differences in their replication capacities. One MPXV isolate which shows the fastest replication kinetics and higher viral loads, possesses a unique non-synonymous mutation (D616L) in the A11L protein (gene OPG136), which encodes for a protein that is part of a major viral core structure. In regard to pandemic preparedness and future outbreaks, we analyzed the antiviral activity of dihydroorotate dehydrogenase (DHODH) inhibitors, and show that they are active against MPXV, vaccinia virus (VACV), and cowpox virus (CPXV) and therefore likely against orthopoxviruses in general. In agreement with that, we also demonstrated that chemical optimization leads to compounds with EC50 values in the sub-nanomolar range, associated with low cytotoxicity, which forms a good basis for future drug development from this chemical series.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Dihydroorotate dehydrogenase inhibitors; Microevolution; Monkeypox virus

Pearls & Oy-sters: SARS-CoV-2 Infection of the CNS in a Patient With Meningeosis Carcinomatosa - Steininger, Philipp; Seifert, Frank; Balk, Stefanie; Kuramatsu, Joji; Kremer, Andreas; Coras, Roland; Engelhorn, Tobias; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Enßer, Armin (Neurology, 2021)
CRIS-Team Scopus Importer:2021-03-26

Prevalence and patterns of HIV drug resistance in patients with suspected virological failure in North-Western Tanzania - Henerico, Shimba; Mikasi, Sello Given; Kalluvya, Samuel Elias; Brauner, Jan M.; Abdul, Seif; Lyimo, Eric; Desderius, Bernard; Korn, Klaus; Korn, Klaus; van Zyl, Gert; Jacobs, Graeme Brendon; Preiser, Wolfgang; et al. (Journal of Antimicrobial Chemotherapy, 2022)
BACKGROUND: More than 15 million people in sub-Saharan Africa receive ART. Treatment failure is common, but the role of HIV drug resistance in treatment failure is largely unknown because drug resistance testing is not routinely done. This study determined the prevalence and patterns of HIV drug resistance in patients with suspected virological failure. MATERIALS AND METHODS: A single high viral load of >1000 viral RNA copies/mL of plasma at any point during ART was considered as suspected virological failure. HIV-1 RNA was extracted from plasma samples of these patients using the QIAamp Viral RNA kit. The protease and part of the RT regions of the HIV pol gene were characterized. RESULTS: Viral load was determined in 317 patients; 64 (20.2%) had suspected virological failure. We successfully genotyped 56 samples; 48 (85.7%) had at least one major resistance-associated mutation (RAM). Common mutations in RT were M184V (75%), T215Y (41.1%), K103N (39.3%), M41L (32.1%), D67DN (30.3%), G190A (28.6%) and A98G (26.8%). No RAMs were detected in ART regimens based on a ritonavir-boosted PI. CONCLUSIONS: The Tanzanian national guidelines define 'virological failure' as two consecutive viral load measurement results, at 3 month intervals, above the WHO threshold (1000 copies/mL). Here, we show that a single viral load above the WHO threshold is associated with high rates of RAMs. This suggests that a single high viral load measurement could be used to predict virological failure and avoid delays in switching patients from first-line to higher genetic barrier second-line regimens.
CRIS-Team Scopus Importer:2022-02-11

Rapid response flow cytometric assay for the detection of antibody responses to SARS-CoV-2 - Lapuente, Dennis; Maier, Clara; Irrgang, Pascal; Hübner, Julian; Peter, Antonia Sophia; Hoffmann, Markus; Enßer, Armin; Ziegler, Katharina; Winkler, Thomas; Birkholz, Torsten; Kremer, Andreas; Steininger, Philipp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)
SARS-CoV-2 has emerged as a previously unknown zoonotic coronavirus that spread worldwide causing a serious pandemic. While reliable nucleic acid–based diagnostic assays were rapidly available, only a limited number of validated serological assays were available in the early phase of the pandemic. Here, we evaluated a novel flow cytometric approach to assess spike-specific antibody responses.HEK 293T cells expressing SARS-CoV-2 spike protein in its natural confirmation on the surface were used to detect specific IgG and IgM antibody responses in patient sera by flow cytometry. A soluble angiotensin-converting-enzyme 2 (ACE-2) variant was developed as external standard to quantify spike-specific antibody responses on different assay platforms. Analyses of 201 pre-COVID-19 sera proved a high assay specificity in comparison to commercially available CLIA and ELISA systems, while also revealing the highest sensitivity in specimens from PCR-confirmed SARS-CoV-2-infected patients. The external standard allowed robust quantification of antibody responses among different assay platforms. In conclusion, our newly established flow cytometric assay allows sensitive and quantitative detection of SARS-CoV-2-specific antibodies, which can be easily adopted in different laboratories and does not rely on external supply of assay kits. The flow cytometric assay also provides a blueprint for rapid development of serological tests to other emerging viral infections
CRIS-Team Scopus Importer:2020-10-30
Keywords: Antibodies; Coronavirus; Flow cytometry; SARS-CoV-2; Serology

Reactivation of HCMV during RT of the brain results in critical illness and early mortality - Frey, Benjamin; Goerig, Nicole; Becker, Ina; Donaubauer, Anna-Jasmina; Korn, Klaus; Überla, Klaus; Schmidt, Manuel; Dörfler, Arnd; Engelhorn, Tobias; Eyüpoglu, Ilker Yasin; Putz, Florian; Semrau, Sabine; et al. (RADIOTHERAPY AND ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-06-18

Results of Tick-Borne Encephalitis Virus (TBEV) Diagnostics in an Endemic Area in Southern Germany, 2007 to 2022. - Steininger, Philipp; Enßer, Armin; Knöll, Antje; Korn, Klaus (Viruses, 2023)
Tick-borne encephalitis virus (TBEV) is the most important tick-transmitted neurotropic flavivirus in Europe and Asia. Our analysis aimed to investigate the contribution of TBEV-specific antibody detection by serological assays and TBEV RNA detection by real-time PCR to the diagnosis of tick-borne encephalitis (TBE). We analyzed data from 3713 patients from 16 years of laboratory TBEV diagnostics in an endemic area in Southern Germany. During this period, 126 cases of TBE were diagnosed. TBEV-specific IgM ELISA tests showed a high clinical sensitivity (96.8%) and a very high clinical specificity (99.7%). In immunocompetent patients, TBE was reliably diagnosed by detection of TBEV IgM antibodies in serum. Intrathecal TBEV IgG antibody synthesis was detected in 46 of 84 (55%) cases by analysis of paired serum and cerebrospinal fluid (CSF) samples. None of the 87 immunocompetent TBE patients tested had detectable TBEV RNA in serum or CSF. In contrast, in two TBE patients without TBEV-specific antibodies, diagnosis could only be made by the detection of TBEV RNA in CSF. Both patients had previously been treated with the B cell-depleting antibody rituximab. Therefore, in patients with CNS infection and humoral immunodeficiency, it is necessary to include TBEV PCR in the diagnostic approach.
EVALuna2:545508

Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic defects in cytotoxicity - Groß, Miriam; Speckmann, Carsten; May, Annette; Gajardo-Carrasco, Tania; Wustrau, Katharina; Maier, Sarah Lena; Panning, Marcus; Huzly, Daniela; Agaimy, Abbas; Bryceson, Yenan T.; Choo, Sharon; Chow, C. W.; et al. (Journal of Allergy and Clinical Immunology, 2021)
Background: Rubella virus–induced granulomas have been described in patients with various inborn errors of immunity. Most defects impair T-cell immunity, suggesting a critical role of T cells in rubella elimination. However, the molecular mechanism of virus control remains elusive. Objective: This study sought to understand the defective effector mechanism allowing rubella vaccine virus persistence in granulomas. Methods: Starting from an index case with Griscelli syndrome type 2 and rubella skin granulomas, this study combined an international survey with a literature search to identify patients with cytotoxicity defects and granuloma. The investigators performed rubella virus immunohistochemistry and PCR and T-cell migration assays. Results: This study identified 21 patients with various genetically confirmed cytotoxicity defects, who presented with skin and visceral granulomas. Rubella virus was demonstrated in all 12 accessible biopsies. Granuloma onset was typically before 2 years of age and lesions persisted from months to years. Granulomas were particularly frequent in MUNC13-4 and RAB27A deficiency, where 50% of patients at risk were affected. Although these proteins have also been implicated in lymphocyte migration, 3-dimensional migration assays revealed no evidence of impaired migration of patient T cells. Notably, patients showed no evidence of reduced control of concomitantly given measles, mumps, or varicella live-attenuated vaccine or severe infections with other viruses. Conclusions: This study identified lymphocyte cytotoxicity as a key effector mechanism for control of rubella vaccine virus, without evidence for its need in control of live measles, mumps, or varicella vaccines. Rubella vaccine–induced granulomas are a novel phenotype with incomplete penetrance of genetic disorders of cytotoxicity.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Cytotoxicity; granuloma; Griscelli syndrome type 2; hemophagocytic lymphohistiocytosis; live vaccine; primary immunodeficiency; rubella virus

SARS-CoV-2 N gene dropout and N gene Ct value shift as indicator for the presence of B.1.1.7 lineage in a commercial multiplex PCR assay - Wollschläger, Paul; Todt, Daniel; Gerlitz, Nadja; Pfaender, Stephanie; Bollinger, Thomas; Sing, Andreas; Dangel, Alexandra; Ackermann, Nickolaus; Korn, Klaus; Enßer, Armin; Steinmann, Eike; Buhl, Michael; et al. (Clinical Microbiology and Infection, 2021)
Objectives: Detection and surveillance of SARS-CoV-2 is of eminent importance, particularly due to the rapid emergence of variants of concern (VOCs). In this study we evaluated if a commercially available quantitative real-time PCR (qRT-PCR) assay can identify SARS-CoV-2 B.1.1.7 lineage samples by a specific N gene dropout or Ct value shift compared with the S or RdRp gene. Methods: VOC B.1.1.7 and non-B.1.1.7 SARS-CoV-2-positive patient samples were identified via whole-genome sequencing and variant-specific PCR. Confirmed B.1.1.7 (n = 48) and non-B.1.1.7 samples (n = 58) were analysed using the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay for presence of SARS-CoV-2 S, RdRp and N genes. The N gene coding sequence of SARS-CoV-2 with and without the D3L mutation (specific for B.1.1.7) was cloned into pCR™II-TOPO™ vectors to validate polymorphism-dependent N gene dropout with the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay. Results: All studied B.1.1.7-positive patient samples showed significantly higher Ct values in qRT-PCR (Δ6–10, N gene dropout on Ct values > 29) of N gene than the corresponding values of S (p ≤ 0.0001) and RdRp (p ≤ 0.0001) genes. The assay reliably discriminated B.1.1.7 and non-B.1.1.7 positive samples (area under the curve = 1) in a receiver operating characteristic curve analysis. Identical Ct value shifts (Δ7–10) were detected in reverse genetic experiments, using isolated plasmids containing N gene coding sequences corresponding to D3 or 3L variants. Discussion: An N gene dropout or Ct value shift is shown for B.1.1.7-positive samples in the Allplex™ SARS-CoV-2/FluA/FluB/RSV™ PCR assay. This approach can be used as a rapid tool for B.1.1.7 detection in single assay high throughput diagnostics.
CRIS-Team Scopus Importer:2021-07-02
Keywords: B.1.1.7; Diagnostic quantitative RT-PCR; Mutation; SARS-CoV-2; VOC

SARS-CoV-2 samples may escape detection because of a single point mutation in the N gene - Ziegler, Katharina; Steininger, Philipp; Ziegler, Renate; Steinmann, Jörg; Korn, Klaus; Enßer, Armin (Eurosurveillance, 2020)
We found that a single nucleotide polymorphism (SNP) in the nucleoprotein gene of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from a patient interfered with detection in a widely used commercial assay. Some 0.2% of the isolates in the EpiCoV database contain this SNP. Although SARS-CoV-2 was still detected by the other probe in the assay, this underlines the necessity of targeting two independent essential regions of a pathogen for reliable detection.
CRIS-Team Scopus Importer:2020-10-23

Successful treatment of COVID-19 infection with convalescent plasma in B-cell-depleted patients may promote cellular immunity - Kremer, Andreas E.; Kremer, Anita; Willam, Carsten; Völkl, Simon; Verhagen, Johan; Achenbach, Susanne; van der Meijden, Edith; Lang, Vanessa; Aigner, Michael; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; et al. (European Journal of Immunology, 2021)
Treatment with convalescent plasma has been shown to be safe in coronavirus disease in 2019 (COVID-19) infection, although efficacy reported in immunocompetent patients varies. Nevertheless, neutralizing antibodies are a key requisite in the fight against viral infections. Patients depleted of antibody-producing B cells, such as those treated with rituximab (anti-CD20) for hematological malignancies, lack a fundamental part of their adaptive immunity. Treatment with convalescent plasma appears to be of general benefit in this particularly vulnerable cohort. We analyzed clinical course and inflammation markers of three B-cell-depleted patients suffering from COVID-19 who were treated with convalescent plasma. In addition, we measured serum antibody levels as well as peripheral blood CD38/HLA-DR-positive T-cells ex vivo and CD137-positive T-cells after in vitro stimulation with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-derived peptides in these patients. We observed that therapy with convalescent plasma was effective in all three patients and analysis of CD137-positive T-cells after stimulation with SARS-CoV-2 peptides showed an increase in peptide-specific T-cells after application of convalescent plasma. In conclusion, we here demonstrate efficacy of convalescent plasma therapy in three B-cell-depleted patients and present data that suggest that while application of convalescent plasma elevates systemic antibody levels only transiently, it may also boost specific T-cell responses.
CRIS-Team Scopus Importer:2021-09-17
Keywords: B-cell deficiency; convalescent plasma; COVID-19; SARS-CoV-2; T-cell immunity

Successful treatment of COVID-19 with convalescent plasma in B-cell depleted patients may promote cellular immunity - Kremer, Andreas; Kremer, Anita; Willam, Carsten; Verhagen, Johan; Achenbach, Susanne; Van Der Meiden, E.; Lang, Vanessa; Aigner, M.; Maier, Clara; Tenbusch, Matthias; Korn, Klaus; Lutzny-Geier, Gloria; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

Therapeutic Drug Monitoring of Long-Acting Rilpivirine and Cabotegravir for Treatment of HIV-1 Infection - A Case Series of Five Patients With One Virologic Failure After Development of Two-Class Resistance - Gerstenberg, Jacob; Klinker, Hartwig; Baier, Michael; Von Braun, Amrei; Seybold, Ulrich; Helbig, Carlotta; Däumer, Martin; Korn, Klaus; Stephan, Christoph; Schleenvoigt, Benjamin T. (Open Forum Infectious Diseases, 2024)
Virologic failure of long-acting rilpivirine/cabotegravir is rare but may result in severely limited treatment options. Known risk factors cannot predict all cases. Therapeutic drug monitoring (TDM) may help identify patients at risk, but reliable thresholds are missing. We report retrospective TDM in a cohort of 5 patients, including 1 virological failure.
CRIS-Team Scopus Importer:2024-10-04
Keywords: cabotegravir; rilpivirine; TDM; two-class resistance; virologic failure

Time Trend in SARS-CoV-2 Seropositivity, Surveillance Detection- and Infection Fatality Ratio until Spring 2021 in the Tirschenreuth County—Results from a Population-Based Longitudinal Study in Germany - Einhauser, Sebastian; Peterhoff, David; Beileke, Stephanie; Günther, Felix; Niller, Hans Helmut; Steininger, Philipp; Knöll, Antje; Korn, Klaus; Berr, Melanie; Schütz, Anja; Wiegrebe, Simon; Stark, Klaus J.; et al. (Viruses, 2022)
Herein, we provide results from a prospective population-based longitudinal follow-up (FU) SARS-CoV-2 serosurveillance study in Tirschenreuth, the county which was hit hardest in Germany in spring 2020 and early 2021. Of 4203 individuals aged 14 years or older enrolled at baseline (BL, June 2020), 3546 participated at FU1 (November 2020) and 3391 at FU2 (April 2021). Key metrics comprising standardized seroprevalence, surveillance detection ratio (SDR), infection fatality ratio (IFR) and success of the vaccination campaign were derived using the Roche N-and S-Elecsys anti-SARS-CoV-2 test together with a self-administered questionnaire. N-seropositivity at BL was 9.2% (1st wave). While we observed a low new seropositivity between BL and FU1 (0.9%), the combined 2nd and 3rd wave accounted for 6.1% new N-seropositives between FU1 and FU2 (ever seropositives at FU2: 15.4%). The SDR decreased from 5.4 (BL) to 1.1 (FU2) highlighting the success of massively increased testing in the population. The IFR based on a combination of serology and registration data resulted in 3.3% between November 2020 and April 2021 compared to 2.3% until June 2020. Although IFRs were consistently higher at FU2 compared to BL across age-groups, highest among individuals aged 70+ (18.3% versus 10.7%, respectively), observed differences were within statistical uncertainty bounds. While municipalities with senior care homes showed a higher IFR at BL (3.0% with senior care home vs. 0.7% w/o), this effect diminished at FU2 (3.4% vs. 2.9%). In April 2021 (FU2), vaccination rate in the elderly was high (>77.4%, age-group 80+).
CRIS-Team Scopus Importer:2022-06-17
Keywords: case fatality ratio; elderly; infection fatality ratio; longitudinal; population-based; SARS-CoV-2; senior care homes; seroprevalence; surveillance detection ratio; vaccination

Tixagevimab/cilgavimab for the prevention of COVID-19 in vaccine-refractory patients with autoimmune diseases: a prospective cohort study. - Minopoulou, Ioanna; Tascilar, Koray; Corte, Giulia; Mutlu, Melek Yalcin; Schmidt, Katja; Bohr, Daniela; Hartmann, Fabian; Manger, Karin; Manger, Bernhard; Korn, Klaus; Kleyer, Arnd; Simon, David; et al. (Rheumatology, 2024)
OBJECTIVES: To investigate the effects of passive immunization with the anti-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) monoclonal antibodies tixagevimab/cilgavimab on humoral responses and on coronavirus disease 2019 (COVID-19) outcomes in vaccine-refractory patients with immune-mediated inflammatory diseases (IMIDs) at high risk of severe COVID-19. METHODS: A prospective cohort study was performed on a cohort of high-risk vaccine-refractory IMID patients treated with a single dose of tixagevimab/cilgavimab (150 mg/150 mg). COVID-19 outcomes as well as serum and salivary anti-SARS-CoV-2 IgG were assessed at baseline and for at least 6 months. Results were compared with an untreated high-risk vaccine-refractory IMID population. Standardized incidence ratios (SIRs) of COVID-19 compared with the general population were calculated for both groups. RESULTS: A total of 38 high-risk IMID patients received tixagevimab/cilgavimab and were compared with 114 untreated high-risk IMID controls. Serum anti-spike IgG increased to 6.6 OD (s.d. 0.8) at day 1 and remained positive up to month 6 [6.3 OD (s.d. 1.4)]. Salivary anti-spike IgG peaked at month 2 [1.6 OD (s.d. 1.1)] and decreased from month 3 [0.8 OD (s.d. 0.3)]. No severe or extended infection was observed in the tixagevimab/cilgavimab group. Compared with the general population, the SIR of COVID-19 in treated patients was 0.76 (95% CI 0.24, 1.58) despite the increased risk profile. The SIR of the control group was 1.51 (95% CI 1.07, 2.02), corresponding to a significantly increased incidence. CONCLUSIONS: Passive immunization with tixagevimab/cilgavimab is safe and effective in inducing anti-SARS-CoV-2 immunity and potentially in preventing COVID-19 in high-risk vaccine-refractory IMID patients. These data provide a proof of concept for the use of monoclonal antibodies as a preventative strategy against SARS-CoV-2 in vulnerable populations.
EVALuna2:540332

Validation of a Parvovirus B19 NAT Assay for Screening of Umbilical Cord Blood for Allogenic Hematopoietic Stem Cell Donation - Steininger, Philipp; Korn, Klaus; Hackstein, Holger; Strasser, Erwin F. (Transfusion Medicine and Hemotherapy, 2023)
Introduction: Parvovirus B19 transmitted by umbilical cord blood (UCB) products may cause severe disease in allogenic hematopoietic stem cell transplant recipients. Thus, commercially available nucleic acid test (NAT) assays for highly sensitive detection of parvovirus B19 DNA validated for the specimen cord blood plasma (CBP) are required to avoid parvovirus B19 transmission by umbilical hematopoietic stem cell preparations. Methods: The multiplex cobas DPX NAT assay was validated for detection of parvovirus B19 DNA in CBP derived from citrate anticoagulated UCB units which have been processed by the Rubinstein method. In total, 363 retained CBP samples pretested negative for parvovirus B19 DNA were prepared for analyzing sensitivity, specificity, and interference of that NAT assay. The 3rd WHO International Standard for parvovirus B19 DNA was used for determining the 95% limit of detection (LOD95) by probit analysis. Results: The validation of the parvovirus B19 NAT assay for CBP demonstrated high sensitivity, specificity, intra- and inter-assay precision. Dilution series and replicate analyses showed a high linearity of the assay with a coefficient of determination above 0.99 and revealed a LOD95 of 17 International Units (IU)/mL (95% confidence interval, 14-44 IU/mL) for parvovirus B19 DNA in CBP samples. Conclusion: The validation of a commercially available parvovirus B19 NAT assay for the specimen CBP demonstrated a high assay performance fulfilling German guidelines and international regulations.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Allogenic hematopoietic stem cell donation; Nucleic acid test screening; Parvovirus B19; Umbilical cord blood

Validation of a SARS-CoV-2 RNA RT-PCR assay for high-throughput testing in blood of COVID-19 convalescent plasma donors and patients - Strasser, Erwin; Steininger, Philipp; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger (Transfusion, 2020)
Background The frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia in blood donors is uncertain. Thus, assays for SARS-CoV-2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data.
CRIS-Team WoS Importer:2020-11-27